1997
DOI: 10.1093/humupd/3.3.255
|View full text |Cite
|
Sign up to set email alerts
|

The role of vascular endothelial growth factor and interleukins in the pathogenesis of severe ovarian hyperstimulation syndrome

Abstract: Ovarian hyperstimulation syndrome (OHSS) is a dramatic complication of ovulation induction. In its most severe form, OHSS is characterized by massive cystic enlargement of the ovaries associated with third space fluid shift, resulting in the formation of ascites and pleural effusion. Ascites developes because of increased peritoneal capillary permeability. In this study we examined the role of vascular endothelial growth factor (VEGF) and interleukins in the pathogenesis of increased capillary permeability. VE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0
7

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(99 citation statements)
references
References 84 publications
2
88
0
7
Order By: Relevance
“…Cytokines and growth factors (interleukins IL-2, IL-6, IL-8, IL-10, IL-18, VEGF) are known to be implicated in the inflammatory processes associated with late follicular maturation, ovulation, corpus luteum function and embryo implantation, as these molecules are present in the aforementioned fluids in women with OHSS. Other substances, such as histamine, prolactin, prostaglandins and renin-angiotensin, have been proposed as participants in OHSS pathophysiology (Rizk et al, 1997) (Table III).…”
Section: The Role Of Vegf In the Pathophysiology Of Ohssmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytokines and growth factors (interleukins IL-2, IL-6, IL-8, IL-10, IL-18, VEGF) are known to be implicated in the inflammatory processes associated with late follicular maturation, ovulation, corpus luteum function and embryo implantation, as these molecules are present in the aforementioned fluids in women with OHSS. Other substances, such as histamine, prolactin, prostaglandins and renin-angiotensin, have been proposed as participants in OHSS pathophysiology (Rizk et al, 1997) (Table III).…”
Section: The Role Of Vegf In the Pathophysiology Of Ohssmentioning
confidence: 99%
“…It has been demonstrated that the ovary is the main source of VEGF and other cytokines produced during hyperstimulation (Rizk et al, 1997;Schenker, 1999), and that increased capillary permeability and ascites are phenomena predominantly related to the ovaries (Blumenfeld et al, 1997). Furthermore, parameters of ovarian activity during stimulation (E 2 levels and number of oocytes retrieved) correlate closely with VEGF gene expression (Doldi et al, 1997).…”
Section: Humansmentioning
confidence: 99%
“…Serum VEGF levels and clinical biological characteristics of this condition (including capillary leakage and leukocytosis), were significantly correlated [35]. VEGF is present in ascitic fluid of women who develop ovarian hyperstimulation syndrome following exogenous gonadotropin stimulation [36,37].…”
Section: Ovarian Hyperstimulation Syndromementioning
confidence: 94%
“…A number of cytokines are associated with the inflammatory process that takes place during the late follicular maturation, ovulation, corpus luteum function, and embryo implantation [11]. Some interleukins may be found in elevated concentration in patients with OHSS, and increased expression of interleukin 6, for example, is associated with increased vascular permeability, hemoconcentration, elevated plasma estradiol concentration, and inhibition of hepatic albumin production [12].…”
Section: Inflammatory Mediatorsmentioning
confidence: 99%